Myopathic changes detected by quantitative electromyography in patients with MuSK and AChR positive myasthenia gravis. (May 2016) - Nikolic, Ana; Basta, Ivana; Stojanovic, Vidosava Rakocevic; Stevic, Zorica; Peric, Stojan; Lavrnic, Dragana
Highlights: Quantitative electromyography (EMG) detected myopathy in the majority of muscle specific tyrosine kinase (MuSK) and acetylcholine receptor (AChR) positive myasthenia gravis (MG) patients. Quantitative EMG is sensitive, but unable to differentiate between MG subgroups. Quantitative EMG should not be used in isolation. It should complement classical EMG in the detection of myopathic changes. Abstract: Myopathic changes are frequent a electrophysiological finding in patients with muscle specific tyrosine kinase (MuSK) positive myasthenia gravis (MG). The aim of this study was to explore the importance of quantitative electromyography (EMG) in the detection of myopathic changes in MuSK MG patients. Classical and quantitative EMG were performed in 31 MuSK and 28 acetylcholine receptor (AChR) positive MG patients, matched by sex, age, disease duration and severity. Classical EMG revealed the presence of myopathic changes more frequently in MuSK MG compared to AChR MG patients, especially in the facial muscles. Quantitative EMG registered myopathic lesions more frequently than classical EMG, but the frequency was similar between MuSK and AChR MG patients. Quantitative EMG revealed myopathic changes in the majority of both MuSK and AChR positive MG patients. This examination is sensitive, but it cannot be used to differentiate between MG patients belonging to the different disease groups. It should not be used in isolation. Rather, it should complement classical EMG in the detection of myopathic changes.